Про нестійкість рівноваги неголоиомних систем - Сосницький, С.П. (Український математичний журнал, 1999)
Встановлено критерій нестійкості рівноваги иеголономних систем, в яких гіроскопічні сили можуть домінувати над потенційними. Показано, що аналогічно до випадку голономиих систем явне домінування гіроскопічних сил над потенційними не є достатнім, щоб забезпечити стійкість рівноваги иеголономних систем. We introduce the notion of CDN[)-groups:G is a CDN[)-group if, for any pair of its subgroupsA andB such thatA is a proper nonmaximum subgroup, ofB, there exists a normal subgroupN which belongs toG and satisfies the inequalitiesA≤N. Fifteen types of nilpotent non-Dedekind groups and nine types of nonnilpotent locally graded groups of this kind are obtained.